Journeying through Dementia, a community-based self-management intervention for people aged 65 years and over: a feasibility study to inform a future trial - Sprange, Kirsty; Mountain, Gail; Shortland, Katy; Craig, Claire; Blackburn, Daniel J.; Bowie, Peter; Harkness, Kirsty; Spencer, Maggie (Biomed Central, 2015)
Background